Let's stop and chat awhile cultural differences in selected yahoo! chat rooms - Calag, Mae Joyce E. 1985-
" The study aimed to determine the distinct patterns of cultural differences manifested in the five Philippine chat rooms of Yahoo! Chat. These were Metro Manila Barkada, Pinoy Chat, Philippines, Overseas Filipino Workers Zone, and Luzon. Both quantitative and qualitatives methods were utilized to gather the data. The researchers had two online methods: the online survey which they launched and the online interview. Their offline method was the focus interview. The main concepts and varibales in the study were: (1) socio-demographics, (2) communication styles, (3) attitudes toward disagreement, (4) approaches to completing tasks of participants and the (5) extent to which respondents reveal personal details about themselves. Data gathered came from those who engage in chat, particularly YM Chat. These comprise of mostly high-income families, males and females alike. Most of them have been using the YM Chat for a long period of time. The most used features of chatters are the emoticons and the acronyms which are representations of the chatter's emotions and short-cut expressions respectively. Findings were consistent with the tenet of the Social Penetration Theory. The chatters simultaneously go through the four stages of relationship process. Personal introductions were common in the orientation stage. There were also incidences of disagreement. However, these were minimal and none of these were resolved. In the exploratory stage, the chatters start to reveal themselves although deception is prevalent. Friendships are formed in the affective stage as evidenced by the presence of clans in the chat rooms. Eyeballs and Grand Eyeballs are common practices. When chatters reach the stable stage, they form visual relationships which they deem comparable to their real relationships. Results of the study showed that there is an element of culture in YM Chat, that is, communication style. However, other elements (i.e., attitude towards disagreement and approaches to completing tasks) cannot be said to exist in a particular, definite manner. Hence, the researchers conclude that a culture particular to YM Chat is nonexistent."